ONTOGENETIC, EPISTEMOLOGICAL, AND DIDACTIC BARRIERS IN LEARNING THE PYTHAGOREAN THEOREM IN SECONDARY SCHOOLS: A SYSTEMATIC LITERATURE REVIEW - Gesa Febrina Gesvania (Journal of Authentic Research on Mathematics Education (JARME), 2026)
The Pythagorean Theorem is a fundamental concept in geometry; however, international assessments such as PISA and TIMSS continue to reveal persistent student difficulties stemming from conceptual, procedural, and contextual barriers. This study aims to identify these barriers, examine their interrelationships, and propose a comprehensive model through a Systematic Literature Review (SLR) following the PRISMA 2020 protocol. A total of 312 articles were initially retrieved from Scopus, Web of Science, ERIC, Google Scholar, DOAJ, and SINTA, with 65 meeting the inclusion criteria and assessed using MMAT 2018, yielding high inter-rater reliability (Cohen's Kappa = 0.87). The results indicate that ontogenetic barriers (68%) are linked to weak prerequisite knowledge and limited visualization skills, epistemological barriers (72%) are characterized by reliance on procedural memorization, and didactic obstacles (54%) reflect insufficient contextualization in instruction. Co-occurrence analysis further demonstrates strong associations between ONT–EPI (0.82) and EPI–DID (0.74), highlighting the cyclical nature of learning barriers. To address this, the ONT–EPI–DID Model was developed, extending the frameworks of Brousseau and Duval while complementing the vicious cycle model of Hiebert. Theoretically, this study contributes a cross-national perspective on learning obstacles, and practically, it provides evidence-based recommendations for diagnostic assessment, visual scaffolding, and contextualized instruction. Overall, the findings underscore the importance of holistic pedagogical interventions to disrupt recurring cycles of difficulty and enhance students' conceptual understanding across diverse educational contexts.